1995
DOI: 10.1016/0735-1097(94)00322-h
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation activity is increased in the left atrium of patients with mitral stenosis

Abstract: The coagulation system is activated in the left atrium of patients with mitral stenosis even during anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
4
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 44 publications
0
44
4
3
Order By: Relevance
“…243 In patients with rheumatic mitral stenosis undergoing trans-septal catheterization for balloon valvuloplasty, levels of fibrinopeptide A, thrombin-antithrombin III complex, and prothrombin fragment F1.2 are increased in the LA compared with the RA and femoral vein, indicating regional activation of the coagulation system. 244,245 Whether such elevations are related to AF, for example, through atrial pressure overload or due to another mechanism has not been determined. Regional coagulopathy is associated with SEC in the LA and hence with atrial stasis.…”
Section: Pathophysiology Of Thrombus Formationmentioning
confidence: 99%
“…243 In patients with rheumatic mitral stenosis undergoing trans-septal catheterization for balloon valvuloplasty, levels of fibrinopeptide A, thrombin-antithrombin III complex, and prothrombin fragment F1.2 are increased in the LA compared with the RA and femoral vein, indicating regional activation of the coagulation system. 244,245 Whether such elevations are related to AF, for example, through atrial pressure overload or due to another mechanism has not been determined. Regional coagulopathy is associated with SEC in the LA and hence with atrial stasis.…”
Section: Pathophysiology Of Thrombus Formationmentioning
confidence: 99%
“…Thirdly, blood samples were not obtained from peripheral veins; however, a previous study clearly demonstrated no difference in coagulation activity between peripheral veins and the SC. 31 Fourthly, some selection biases may be present between the discontinuous and continuous warfarin groups. A randomized trial is necessary to increase the accuracy of the present results.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The size of the LAA 9,10,11,12 and the presence of spontaneous echo contrast 13,14,15,16,17 are considered positive predictors of LA thrombus. Mitral valve area (MVA) is inversely related to the presence of spontaneous echo contrast (SEC) 6,18,19,20,21,22 . Atrial fibrillation (AF) which occurs in more than 40% of patients with MS later in the course of the disease carries a 17-fold increased risk of thromboembolism 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Emboli can be recurrent and multiple in up to a quarter of patients 3 . A pro-thrombotic state exists in the left atrium (LA) in patients with MS even with appropriate anticoagulation therapy 5,6 . The left atrial appendage (LAA) is the commonest site of thrombus formation 7,8 .…”
Section: Introductionmentioning
confidence: 99%